Human CD45RA− FoxP3hi Memory‐Type Regulatory T Cells Show Distinct TCR Repertoires With Conventional T Cells and Play an Important Role in Controlling Early Immune Activation. Issue 10 (18th May 2015) - Lei, H.; Kuchenbecker, L.; Streitz, M.; Sawitzki, B.; Vogt, K.; Landwehr‐Kenzel, S.; Millward, J.; Juelke, K.; Babel, N.; Neumann, A.; Reinke, P.; Volk, H.‐D.
Abstract : Adoptive immunotherapy with regulatory T cells (Treg) is a new option to promote immune tolerance following solid organ transplantation (SOT). However, Treg from elderly patients awaiting transplantation are dominated by the CD45RA − CD62L + central memory type Treg subset (TregCM), and the yield of well‐characterized and stable naïve Treg (TregN) is low. It is, therefore, important to determine whether these TregCM are derived from the thymus and express high stability, suppressive capacity and a broad antigen repertoire like TregN. In this study, we showed that TregCM use a different T cell receptor (TCR) repertoire from conventional T cells (Tconv), using next‐generation sequencing of all 24 Vβ families, with an average depth of 534 677 sequences. This showed almost no contamination with induced Treg. Furthermore, TregCM showed enhanced suppressive activity on Tconv at early checkpoints of immune activation controlling activation markers expression and cytokine secretion, but comparable inhibition of proliferation. Following in vitro expansion under mTOR inhibition, TregCM expanded equally as well as TregN without losing their function. Despite relatively limited TCR repertoire, TregCM also showed specific alloresponse, although slightly reduced compared to TregN. These results support the therapeutic usefulness of manufacturing Treg products from CD45RA − CD62L + Treg‐enriched starting material to be applied for adoptive Treg therapy. Abstract : The shift to memory‐type regulatory T cells in elderly probands and patients on the transplant waitlist is not a limitation to generate regulatory T cell products with high yield and functional activity, even if the T cell receptor repertoire is biased and the frequency of alloreactive clones might be reduced.